UJI VALIDITAS DAN RELIABILITAS MULTIPLE CHOICE QUESTIONS PADA INSTRUMEN UJI KOMPETENSI KADER POSYANDU DI ERA TRANSFORMASI PELAYANAN KESEHATAN PRIMER - Bastian, Ardi; YULIAWATI, RIZA; AGUSTINA, UKIK; Sari, Reny Mareta (Journal of Hospital Administration and Management (JHAM), 2025)
The implementation of the Posyandu cadre competency test in Indonesia still uses interviews and direct observation methods by health workers. This method requires a long time, requires a lot of human resources, and has the potential subjectivity in the assessment. Therefore, a cadre assessment  method has been developed using a multiple-choice questions (MCQs) instrument. This study aims to test the validity and reliability of the developed multiple-choice questions (MCQs) instrument. The research method uses quantitative descriptive to analyze the validity and reliability of MCQs for Posyandu cadre competency tests. Validity analysis was carried out using content validity by 2 experts, face validity by 11 cadres and health workers, and construct validity using product moment which was tested on 186 cadres. Meanwhile, the reliability test used Cronbach's alpha. The results of the validity test showed that content validity resulted in findings that the questions on the instrument did not cover all the knowledge being tested, the questions and answer choices were too long, and still used language that was too academic. Meanwhile, face validity found that there were unknown and confusing word choices by the cadres, and from construct validity it was found that out of 145 questions tested, there were 32 invalid questions. From the reliability test, it showed that all 145 questions were reliable (alpha cronbach between 0.70 - 0.90). The conclusion of this study is the MCQs instrument that has been tested for validity and reliability can be used as a competency test method for Posyandu cadres throughout Indonesia.